How much has the game changed? Revisiting policymaking in Latin America a decade later - Mark P. Jones (Inter-American Development Bank (IDB), 2017)
In the early 2000s the Inter-American Development Bank launched a visionary and influential research agenda that dramatically improved understanding of the policymaking process (PMP) in Latin America. It did so by detailing the role played by key actors in the PMP and how those actors interacted to produce public policy throughout the region in general, and, via the publication of a volume in English and an updated version in Spanish, in eight countries (Argentina, Brazil, Chile, Colombia, Ecuador, Mexico, Paraguay, Venezuela) in particular. This paper reviews the degree to which these eight country-level analyses still accurately portray the actors and their role in the PMP today. It concludes that in a large majority of the countries the analysis is still broadly valid and accurately describes the political institutions and actors who are pivotal for the policymaking game, although in some areas the original analysis would benefit from revision and update.
hdl:11319/8115
Keywords: D72; D78; 330; Policy processes; Policy formulation; Policymaking process